KESULITAN DALAM BELAJAR: ANALISIS FAKTOR PENYEBAB DAN STRATEGI PENANGANAN DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN DAN PENDIDIKAN ISLAM - Muhammad Fatih Husna (JIEGC Journal of Islamic Education Guidance and Counselling, 2026)
Learning difficulty is a persistent problem throughout the educational process, from the elementary level through higher education. Prior studies, ranging from local case studies to international systematic reviews, have identified causal factors and intervention models for learning difficulties, yet they generally treat the psycho-pedagogical and the religious-spiritual dimensions separately, leaving a conceptual gap for the management of Islamic education. This article aims to fill that gap by constructing a critical synthesis between contemporary educational-psychology findings (2021–2025) and Islamic educational values in explaining the nature, classification, causal factors, impact, and management strategies of learning difficulties. The paper employs a narrative literature review method with a structured search across SINTA, Google Scholar, ERIC, and Scopus-indexed international journals, guided by explicit inclusion-exclusion criteria. The findings show that learning difficulties arise from a complex interaction of internal (physiological-psychological) and external (family, school, community) factors, corroborated by recent empirical evidence on the role of academic self-concept, family support, and inclusive learning environments. From an Islamic perspective, learning difficulty is understood as part of the natural diversity of human fitrah, requiring educators to act with patience, wisdom, and the principle of tadarruj (gradualness). This article's conceptual contribution lies in an integrative framework linking modern educational-psychology evidence with the values of itqan and muhasabah, together with a recommended agenda for further empirical research testing the effectiveness of an integration-based management model for learning difficulties.